Lingering risk: A meta-analysis of outcomes following primary total knee arthroplasty for patients with post-traumatic arthritis. (May 2020) - Liu, Yang; Zhao, Xiao-Dan; Zou, Chang
Abstract: Background: Currently, no meta-analysis exists to elucidate the outcomes of primary total knee arthroplasty (TKA) in patients with post-traumatic arthritis (PTA). The primary aim of this meta-analysis was to compare revision and complication rates for patients with PTA versus osteoarthritis (OA). Methods: The following databases were used for searching existing literature (from their inception to October 2019): PubMed, Scopus, EMBASE, Cochrane Library, and Web of Science. The primary outcomes were the incidences of revision and complications, Secondary outcomes included operative time and patient-reported outcomes (PRO) scores. Results: Nine studies with a total of 6, 783, 990 patients were included. This study found that there was a statistically significant difference in the rates of superficial wound infection, periprosthetic infection, stiffness, wound complications, and revision, with these outcomes occurring more frequently in patients with PTA. However, PTA did not increase the risks for periprosthetic fracture, aseptic loosening or instability, and VTE. Moreover, PTA was associated with increased operative time, worse postoperative PRO scores, and similar changes in PRO scores. Conclusions: This meta-analysis highlight the complexity of PTA and demonstrates increased risks of infection, wound complications, stiffness, and revision. Surgeons can use this information to help aid in counseling patients preoperatively. Highlights: Patients with PTA are at increased risk for infection, stiffness, and revision as compared to patients with OA. PTA did not increase the risks for periprosthetic fracture, aseptic loosening or instability, and VTE. PTA was associated with increased operative time, worse postoperative PRO scores, and similar changes in PRO scores.